2011
DOI: 10.1002/adma.201100806
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Color‐Tunable Light‐Emitting Diodes

Abstract: Visible‐color‐tunable light‐emitting diodes (LEDs) with electroluminescent color that changes continuously from red to blue by adjusting the external electric bias are fabricated using multifacetted GaN nanorods with anisotropically formed 3D InGaN multiple‐quantum wells. Monolithically integrated red, green, and blue LEDs on a single substrate, operating at a fixed drive current, are also demonstrated for inorganic full‐color LED display applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
256
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(266 citation statements)
references
References 30 publications
10
256
0
Order By: Relevance
“…This is corroborated by the findings of Fichtenbaum et al 132 Recently, Hong et al reported a visible-color tunable LED with core-shell GaN nanorod arrays. 134 The GaN nanorod arrays were grown on patterned SiO 2 /n þ GaN/sapphire templates. Then, the InGaN/GaN MQWs and p-GaN were overgrown on the GaN nanorod arrays.…”
Section: B Bottom Up Axial Nanoledsmentioning
confidence: 99%
“…This is corroborated by the findings of Fichtenbaum et al 132 Recently, Hong et al reported a visible-color tunable LED with core-shell GaN nanorod arrays. 134 The GaN nanorod arrays were grown on patterned SiO 2 /n þ GaN/sapphire templates. Then, the InGaN/GaN MQWs and p-GaN were overgrown on the GaN nanorod arrays.…”
Section: B Bottom Up Axial Nanoledsmentioning
confidence: 99%
“…20,21 In addition, a major challenge remains in the vdW epitaxy of semiconductors on hBN: precise control of the position, size and shape of the semiconductor nanostructures, all of which are critical for monolithic microelectronic processing. [22][23][24][25][26] In this article, we report on the maskless shape-controlled vdW heteroepitaxy of ZnO nanostructures on hBN substrates in a designed manner using the artificially formed atomic ledges on hBN. Electron microscopic analyses and first-principles theoretical calculations exhibit how the highly lattice-mismatched ZnO/hBN heterojunction is fabricated to be of high quality using vdW epitaxy.…”
Section: Introductionmentioning
confidence: 99%
“…The TEM/STEM clearly show significantly large differences in the QW and QB thickness on different growth facets, which may be a result of the anisotropic surface formation energies of GaN crystal planes that are known to influence the diffusion of adatoms. 15,[53][54] The nanorods scratched off for the CL analysis were investigated by STEM as shown in Fig. 5d-e.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13] These dislocation free GaN nanostructures are also reported to increase light extraction efficiency and enlarge the light emitting surface. [14][15][16] Additionally moving from bulk to nanoscale provides many new optical properties [17][18] bridging the green gap.…”
Section: Introductionmentioning
confidence: 99%